Secreted phospholipase A(2) is increased in meconium-stained amniotic fluid of term gestations: potential implications for the genesis of meconium aspiration syndrome - Romero, Roberto (J Matern Fetal Neonatal Med, 2014)
BACKGROUND: Meconium-stained amniotic fluid (MSAF) represents the passage of fetal colonic content into the amniotic cavity. Meconium aspiration syndrome (MAS) is a complication that occurs in a subset of infants with MSAF. Secreted phospholipase A(2) (sPLA(2)) is detected in meconium and is implicated in the development of MAS. The purpose of this study was to determine if sPLA(2) concentrations are increased in the amniotic fluid of women in spontaneous labor at term with MSAF. MATERIALS AND METHODS: This was a cross-sectional study of patients in spontaneous term labor who underwent amniocentesis (n = 101). The patients were divided into two study groups: (1) MSAF (n = 61) and (2) clear fluid (n = 40). The presence of bacteria and endotoxin as well as interleukin-6 (IL-6) and sPLA(2) concentrations in the amniotic fluid were determined. Statistical analyses were performed to test for normality and bivariate analysis. The Spearman correlation coefficient was used to study the relationship between sPLA(2) and IL-6 concentrations in the amniotic fluid. RESULTS: Patients with MSAF have a higher median sPLA(2) concentration (ng/mL) in amniotic fluid than those with clear fluid [1.7 (0.98–2.89) versus 0.3 (0–0.6), p < 0.001]. Among patients with MSAF, those with either microbial invasion of the amniotic cavity (MIAC, defined as presence of bacteria in the amniotic cavity), or bacterial endotoxin had a significantly higher median sPLA(2) concentration (ng/mL) in amniotic fluid than those without MIAC or endotoxin [2.4 (1.7–6.0) versus 1.7 (1.3–2.5), p <0.05]. There was a positive correlation between sPLA(2) and IL-6 concentrations in the amniotic fluid (Spearman Rho=0.3, p <0.05). CONCLUSION: MSAF that contains bacteria or endotoxin has a higher concentration of sPLA(2), and this may contribute to induce lung inflammation when meconium is aspirated before birth.